Some Practical Applications of Ore Microscopy at Les Mines Selbaie, Quebec - I. G. L. Sinclair (The Minerals, Metals and Materials Society, 1989)
The Selbaie deposit is located in northern Quebec. It is comprised of three distinct, but genetically related, Cu-Zn-Ag ore bodies which also contain economically significant amounts of Au. The deposits are Archean in age and volcanogenic in origin. At Selbaie, ore microscopy has been employed to aid in planning of ore beneficiation methods and to monitor the ongoing performance of the concentrator. Examples of both types of study are described. Early in the life of the mine, excessive amounts of Zn appearing were found to be appearing in the Cu concentrate. Microscopic examination of concentrates showed that this was being caused by the presence of coatings of supergene chalcocite on sphalerite grains. Fine coatings of supergene galena and chalcopyrite were also observed on some sphalerite grains. The presence of Ag and Au in the ores makes an important contribution to the revenue of the mine. The various modes of occurrence and mineralogical relationship of these two metals are described and discussed. Monitoring of the ongoing concentrating process at selbaie is done by qua-litative and quantitative examination of products collected at various points along the circuit. Causes of such problems as excessive loss of metals to the tailings or inefficient recovery of individual metals, can often be identified and possible solutions proposed.